(untitled) (Belügyi Szemle, 2025)
Aim: The aim of the article is to review and understand how the crime of armed kidnapping was present in the latest 30 years in Hungary, including various types of statistics and their comparison. Methodology: Different types of statistical methods were used during the examination which were based on data requested from the Ministry of Interior, from the National Office of the Judiciary and from the Prosecution Service of Hungary. Furthermore, the legal background was reviewed and compared to the results of the statistical research. Findings: Results show that even though armed kidnapping is a rare crime in Hungary, there are several similarities between the perpetrators in socioeconomic statuses and their crimes. Armed kidnapping was mostly committed in Budapest by two perpetrators at the same time who finished the crimes. These perpetrators were mostly Hungarian citizens, adults, males and singles without any children with a clean criminal record. Value: The results may help to reduce occurrences of armed kidnapping and, in cases of armed kidnapping being committed, help the investigative authorities to understand and register these cases better – furthermore to provide help to the courts when deciding upon these cases to create a coherent and consistent judicial practice.